Development of a Li2O Sensor Based on a Yttria Stabilized Zirconia Membrane for Oxide Reduction in a Molten LiCl-Li2O Electrolyte at 650°C. (2nd April 2020) - Cao, G.; Herrmann, S.; Li, S.; Hoover, R.; King, J.; Serrano-Rodriguez, B.; Marsden, K.
Abstract: LiCl-Li2 O salt is a widely used electrolyte for the electrochemical reduction of spent oxide (mainly uranium oxide) fuels, and the Li2 O concentration is usually controlled at about 1.41 mol % for optimum operation and corrosion mitigation of the platinum anode material. Due to the small difference in reduction potential between UO2 and Li2 O, some Li2 O will be reduced during the oxide reduction process, leading to a Li2 O deviation from the desired 1.41 mol %. Monitoring of the Li2 O concentration is desired for proper control of the electrochemical oxide reduction process. In this paper, a Li2 O sensor based on a yttria stabilized zirconia (YSZ) membrane was developed and tested to evaluate the feasibility of using the Li2 O sensor to monitor the Li2 O concentrations in the range of 0.57 to 1.69 mol % Li2 O in LiCl-Li2 O salt systems—one without dissolved Li metal and another with 0.24 mol % dissolved Li metal. The experimental results show that the open circuit potential of the Li2 O sensor logarithmically responded to the concentration of Li2 O in LiCl-Li2 O salts with or without the presence of Li metal, suggesting that YSZ appears promising for real-time monitoring of the Li2 O concentration in LiCl-Li2 O salt for an oxide reduction process. The Li2 O sensor developed herein is based on a potentiometry measurement that requires a stable, reliable reference electrode (RE), particularly for long-term Li2 O concentration monitoring. To this end, a novel Ag/AgCl RE that is contained in a high-density MgO tube with a closed end was developed and exhibited stable electrode potential, chemical compatibility with LiCl-Li2 O, and good mechanical strength. The performance of the newly developed Ag/AgCl RE was demonstrated in Li2 O monitoring by comparing it with a traditional Ni/NiO RE.